Rail demand management: towards developing effective strategies for extended mega urban regions in Malaysia - Mohd Mahudin, Nor Diana (2013)
Rail overcrowding has been associated with a number of negative consequences, including psychological stress, adverse health effects, negative behavioural reactions, and spillover effects. Despite the seriousness of this issue, there is little consensus on the appropriate demand management strategies to sufficiently cope with the increasing passenger numbers, particularly on rail services in mega urban regions in Malaysia. This, in turn, warrants a closer examination of existing scientific research and corresponding evidence. In order to evaluate this situation, a review of existing demand management strategies in rail passenger systems was conducted. Key issues and constraints within the rail industry are identified and a set of potential demand management strategies that can help reduce rail overcrowding is suggested. Implications of the results are discussed in terms of their effectiveness and feasibility, particularly for rail operators and policy makers in addressing future challenges and peak demand growth through a more structured, comprehensive, and sustainable approach.